TLC, ESR, CRP & Procalcitonin: Markers for prognosis in Musculoskeletal infections of Children (Journal of Pharmaceutical Negative Results, 2023)
BACKGROUND: Musculoskeletal infections in pediatric age group account for 23% of the total infections. The most common musculoskeletal infections in children are Osteomyelitis and Septic Arthritis. Such children with underlying present with fever, inflammation, failure to thrive, refusal to feed, inability to bear weight, limp, Limb pain, swelling, restricted motion at joints. Total Leucocyte Count (TLC), Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are among the oldest laboratory tests used to detect inflammation in the body. Procalcitonin (PCT), a propeptide of calcitonin, is an important host response biomarker indicative of infection. In this context this study was done to evaluate change in severity of inflammation in patients of musculoskeletal infections.MATERIAL AND METHODS: Patients who attended ortho OPD were included after they were diagnosed as a case of musculoskeletal infection. Treatment was started and baseline investigations were done. Medical/ Surgical treatment was given. TLC,ESR , CRP & PCT were checked at the time of admission and at 3 months, 6 months and 9 months for treatment outcomes.STATISTICAL ANALYSIS: Both Descriptive and inferential statistics were applied to the data. Demographic characteristics were expressed as proportion. The values of TLC,ESR,CRP & PCT were compared using paired t test. All statistical analysis was done at 5% significance.RESULTS: A total of 130 patients were evaluated over a period of 9 months of which 63% were male, 37% were female. Abscesses were in 37% cases , 28% were diagnosed as Septic Arthritis, 18% were Osteomyelitis, 9% were transient synovitis followed by 4% skeletal tuberculosis, 3% cellulitis and 1% tetanus. The overall decline in all the four inflammatory markers over 9 months was statistically significant (p<0.00001).CONCLUSIONS: TLC, ESR, CRP & Procalcitonin are good indicators of musculoskeletal infections. Over a period of 9 months with medical/surgical treatment, these markers declined gradually indicating that the infection has subsided.